KONSTRIBUSI KINERJA KEUANGAN TERHADAP HARGA SAHAM DALAM MENDUKUNG EKONOMI BERKELANJUTAN - Ashari Sofyaun; Asrid Juniar; Rini Rahmawati; Eliana G. Malik (Jurnal GeoEkonomi, 2024)
This research aims to measure the contribution of financial performance to stock prices in supporting sustainability economic growth in Pharmaceutical Sub-Sector companies on the Indonesia Stock Exchange in 2018-2022. Total population is 12 company and based on the criteria there is a sample of 8 companies. Data analysis using SmartPLS version 3, research results show that the Current Ratio has a negative effect on stock prices. Partially Return On Assets, Total Asset Turnover have a positive effect on stock prices. Debt To Equity Ratio has no effect on share prices. Partially, Current Ratio, Debt To Equity Ratio and Total Asset Turnover have no effect on Return On Assets. The mediation review shows that the Current Ratio, Debt To Equity Ratio and Total Asset Turnover have no effect on stock prices mediated by Return on Assets.